Efficacy of low dose aspirin on maternal and foetal outcome in preeclampsia - Togarikar, Sopanrao Malharrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Low dose aspirin administration can reduce vasoconstriction and decreases thrombosis of the vessels related to placenta, thereby increases blood flow and protects against to pregnancy related complication like preeclampsia, IUGR or FGR. This study was undertaken to assess the efficacy of low dose aspirin (75 mg/day) on foetal and maternal outcome in preeclampsia patients. Methods: A total 100 preeclampsia patients were elected and were divided in to two groups i.e. control group includes age and parity matched preeclampsia cases under regular conventional treatment without aspirin administration and cases group receiving conventional treatment with aspirin 75 mg/ day after breakfast from recruitment upto one week before pregnancy. Results: There was a significant decrease in caesarean sections in cases (22%) and control groups (30%). Blood pressure, proteinuria was significantly reduced and platelets count was increased at time of presentation to after delivery in cases and controls. There was a less intra uterine deaths (8% in cases and 14% in controls) and neonatal deaths (2% in cases and 6% in controls) in cases than in controls. Neonatal haemorrhage was not accounted in both groups. Conclusions: Beginning of low dose aspirin administration in the early second trimester of pregnancy may reduce incidence of adverse health outcomes like IUGR, preeclampsia and preterm birth.